The role of digital skills, digital self-efficacy, and government support in enhancing digital work readiness - Suhada, Suhada; Wulandari, Novi Diah; Idries, Fahmi Akbar; Pratiwi, Nurna; Oktariantra, Ibra; Romandhani, Adinda Octa; Riyadho, Ananda (Asian Management and Business Review, 2026)
This study aims to examine and analyze the influence of digital skills (DS) on digital work readiness (DWR) among youth, with digital self-efficacy (DSE) as a mediating variable and government digital support (GDS) as a moderating variable. Given the rapid pace of digital transformation reshaping the labor market, understanding the interplay between technical competencies and psychological empowerment is crucial, particularly for young job seekers. A quantitative survey was employed involving 200 respondents aged 18–35 years old in Yogyakarta, Indonesia. Data were analyzed using the partial least squares structural equation modeling (PLS-SEM). The findings indicate that DSE is strongly and significantly impacted by DS. Nevertheless, DWR is not directly impacted by DS. Rather, DSE plays a crucial function as a psychological facilitator by fully mediating the link between DS and DWR. However, the statistically insignificant moderating effect of GDS on the relationship between DS and DWR indicates that this pathway is not strengthened by GDS. This study is context-specific to youth in the Yogyakarta region and focuses solely on the integration of DS, DSE, and GDS in predicting DWR. Further research could expand the demographic scope and incorporate additional socio-contextual factors to deepen understanding of digital employability. This study contributes a novel empirical model by integrating both psychological and institutional dimensions into the analysis of DWR. It challenges the conventional reliance on technical training alone and underscores the critical need for confidence-building and GDS to enhance youth employability.